2023
DOI: 10.1002/smll.202300594
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid‐Crosslinked Supramolecular Nanoassembly with Self‐Regulated Photodynamic and Anti‐Metastasis Properties for Synergistic Photoimmunotherapy

Abstract: for overcoming the limitation facing traditional nanocarrier, but three stand out. Cyclodextrins come as a particular boon to hydrophobic chemodrugs, whose solubility can be notably improved by hostguest interaction. Another benefit arises from facile modification of such functional groups as targeting ligands, therapeutic or imaging agents into the building blocks. In addition, driven by dynamic and reversible host-guest recognition, these assemblies respond to a wide range of physiologic stimulus, like pH, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…H 2 O 2 ‐responsive nanomaterials combined with photodynamic therapy (PDT) have shown great potential in TNBC treatment (Yang et al, 2020). Zhou et al, utilized chlorine e6 (Ce6)‐conjugated β‐cyclodextrin and ferrocene‐containing phenylboronic acid to construct a PDT nanoparticle bound to redox response (Zhou, Zhang, et al, 2023). Under laser irradiation, CPR produced a large amount of ROS to damage tumor cells and induced immunogenic cell death (ICD).…”
Section: Design Ideas For Np‐drug Delivery Systems Responsive To the ...mentioning
confidence: 99%
“…H 2 O 2 ‐responsive nanomaterials combined with photodynamic therapy (PDT) have shown great potential in TNBC treatment (Yang et al, 2020). Zhou et al, utilized chlorine e6 (Ce6)‐conjugated β‐cyclodextrin and ferrocene‐containing phenylboronic acid to construct a PDT nanoparticle bound to redox response (Zhou, Zhang, et al, 2023). Under laser irradiation, CPR produced a large amount of ROS to damage tumor cells and induced immunogenic cell death (ICD).…”
Section: Design Ideas For Np‐drug Delivery Systems Responsive To the ...mentioning
confidence: 99%
“…[ 29 ] For instance, Yang Zhou et al reported a rosmarinic acid–cross‐linked supramolecular nanoassembly that can regulate the level of PDT‐induced reactive oxygen species (ROS) and inhibit epithelial–mesenchymal transition (EMT), so that the damage to normal tissue be diminished while the cytotoxicity to tumor cells is preserved. [ 30 ] Rou Xie et al have proposed an acid‐triggered self‐assembled gold nanoparticle targeted at heat shock protein 70 that is expressed on the membrane of glioma cells, thus selectively transporting doxorubicin that was encapsulated inside the nanoparticles into glioma. In vivo experiments showed that when in combination with PD‐1 checkpoint blockade, powerful synergistic effects would take place accompanied with the multiplication of mature dendritic cells (DCs), cytotoxic T‐lymphocytes (CTLs) and survival time.…”
Section: Immunotherapymentioning
confidence: 99%
“…In recent years, CFDDSs have been developed with high drug-loading capacity, low off-target toxicity, and minimal immunogenicity for cancer treatment. [12][13][14] Further, self-assembly technology holds enormous potential for the development of new drugs. 15,16 In self-assembled nanodrug delivery systems (SANDDSs), NSMs form nanocarrier complexes spontaneously through non-covalent bonds (including van der Waals forces, hydrogen bonds, π-π stacking, halogen bonds, hydrophobic interactions, cation-π bonds, ionic bonds, CH-π bonds and solvation) under equilibrium conditions and can be combined with photosensitizers or other drug molecules to form nano-sized multifunctional drug complexes targeting tumor tissues.…”
Section: Introductionmentioning
confidence: 99%